2022
DOI: 10.3390/antibiotics11060795
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication with Antibiotics: Prevalence, Practices and Related Factors among the Pakistani Public

Abstract: Self-medication with antibiotics (SMA) has become considerably common in developing countries, which is a critical factor for driving antibiotic resistance. Individuals involved in SMA generally do not have adequate knowledge regarding the appropriate use, indications and dosage of these drugs. The objective of the present study was to investigate population SMA practices, knowledge and sociodemographic factors associated with SMA in Islamabad, Pakistan. The study adopted a cross-sectional methodology and data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…5 Our results showed community pharmacies is the largest provider (93.3%) of antibiotics, and the rest from previous prescriptions which are comparable to other studies from subcontinent. 11,6 Leftover drugs, are the source of drugs in the study by Nepal et al 5 The 70% of our study participants responded that the sometimes check the package before consuming the medication. Completion of the medicine, followed by disappearing of symptoms are the most common reason for stopping the medicine in our study and Study from Kerala, whereas disappearance of symptoms remains the first reason on a more global scenario.…”
Section: Discussionmentioning
confidence: 78%
“…5 Our results showed community pharmacies is the largest provider (93.3%) of antibiotics, and the rest from previous prescriptions which are comparable to other studies from subcontinent. 11,6 Leftover drugs, are the source of drugs in the study by Nepal et al 5 The 70% of our study participants responded that the sometimes check the package before consuming the medication. Completion of the medicine, followed by disappearing of symptoms are the most common reason for stopping the medicine in our study and Study from Kerala, whereas disappearance of symptoms remains the first reason on a more global scenario.…”
Section: Discussionmentioning
confidence: 78%
“…In Brazil, a higher prevalence of 34% for LA was observed, with a particularly strong association with amoxicillin + clavulanate at 42%, similar to our study's findings of 36.89% [ 24 ]. Furthermore, a global survey of LA in 11 countries discovered a prevalence of 51.9% among respondents who obtained antibiotics through new prescriptions or from medical professionals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“… 20 A cross-sectional study from Pakistan assessing the sociodemographic factors associated with antibiotic self-medication revealed that approximately 70% of survey participants had used antibiotics over the past year and 30% without consultation with a healthcare professional. 20 Similarly, a survey of 5 countries in Africa revealed that antibiotics are among the most frequently prescribed medications, with 90% of individuals with acute illness seeking care and 36% being prescribed antibiotics. About 30% of these patients received antibiotics without prescriptions and 25% received antibiotics from informal dispensers.…”
Section: The Challenges Of Implementing Antimicrobial Stewardship Pro...mentioning
confidence: 99%